Women Entrepreneurial Growth and Business Sustainability: A Comparative Study of Self-Help Groups (SHGs) in India - Debashree Chakraborty (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Over the years several initiatives have been taken by the Government of India to empower the women of our country and increase their participation in the labor force. In this context, the paper considers the role of women’s cooperatives, in the form of Self-help Groups (SHGs) that have been playing crucial role in empowering women at the grassroot level and bolstering the rural social and financial institutions of the country. The objective of the article is to review existing studies on the role of female SHGs in rural sector in fostering women empowerment through women entrepreneurship and highlight emerging challenges. The article also traces the sustainability of the business models of the SHGs and identifies the hindrance that lies in the way of better market integration and financial inclusion. It concludes by looking at the future prospects of SHGs in elevating rural economy by generating income and employment opportunities for female through entrepreneurial capacity building.